The Effect of Financial Leverage on Earnings Per Share and Return on Equity: JEL Classification: G21, G32, M41, C12, G33 - Hasriani, Hasriani; Sugianto, Sugianto; Nursyamsuriana, Nursyamsuriana; Sutriana, Sutriana; Mauna, Randy; Jumriani, Jumriani (Newinera Publisher, 2025)
This study aims to analyze the effect of financial leverage on earnings per share (EPS) and return on equity (ROE) in the banking sector of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2020-2024. Financial leverage is measured using the debt-to-equity ratio, while EPS and ROE are used as indicators of the company's financial performance. The research method used is quantitative with an ex post facto approach, utilizing secondary data obtained from annual financial reports for the 2020-2025 period. Data analysis was conducted using a simple linear regression test to measure the relationship and effect of financial leverage on EPS and ROE. The results show that financial leverage has a significant and negative effect on EPS in SOE banking companies listed on the Indonesia Stock Exchange (IDX). This indicates that loan interest expenses erode net income per share, thereby reducing shareholder welfare, and that the debt financing structure is not offset by increased interest income or operational efficiency. Financial leverage does not have a significant and positive effect on ROE in SOE banking companies listed on the IDX, indicating that banking management is able to maintain equity profitability despite increases or decreases in leverage levels.